2006
DOI: 10.1007/s00117-005-1241-y
|View full text |Cite
|
Sign up to set email alerts
|

Ist die Röntgenthoraxaufnahme bei Neueinstellungen gerechtfertigt?

Abstract: The performance of chest radiography as part of a PEE is most often not justified. The practice is expensive, can violate national and European law, and lacks medical justification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They concluded that this practice is expensive and could also be in violation of European law. [ 7 ] Lohiya et al . [ 8 ] and Abuchi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that this practice is expensive and could also be in violation of European law. [ 7 ] Lohiya et al . [ 8 ] and Abuchi et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] There has been a lot of discussion regarding the usefulness or the futility of routine chest radiographs as part of screening of prospective employees, with some studies concluding in favor[ 3 4 ] and others against such practice. [ 5 6 7 8 9 10 11 12 13 14 15 ] To our knowledge, there is no published data from India on this subject.…”
Section: Introductionmentioning
confidence: 99%